2010
DOI: 10.1021/ic100795p
|View full text |Cite
|
Sign up to set email alerts
|

Catalytically Stable and Active CeO2 Mesoporous Spheres

Abstract: A facile one-step strategy has been developed for preparing monodisperse CeO(2) mesoporous spheres with high surface areas, uniform size distributions, and well-defined pore topologies. These mesoporous spheres have been demonstrated to be catalytically stable and active for CO oxidation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
100
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 136 publications
(102 citation statements)
references
References 20 publications
2
100
0
Order By: Relevance
“…under oxidizing and reducing conditions, respectively [2,3]. However, the CeO 2 is not a promising candidate for catalytic samples mainly due to its low catalytic activities [4][5][6][7][8][9]. Numerous reports have shown that the activity of ceria in total oxidation reactions is greatly enhanced by transitional metals like Co, Cu, Ti, Ni, and so on [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…under oxidizing and reducing conditions, respectively [2,3]. However, the CeO 2 is not a promising candidate for catalytic samples mainly due to its low catalytic activities [4][5][6][7][8][9]. Numerous reports have shown that the activity of ceria in total oxidation reactions is greatly enhanced by transitional metals like Co, Cu, Ti, Ni, and so on [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous CeO 2 synthesis procedures have been reported in literature [10][11][12][13] leading to various nanoparticle morphologies. These materials were extensively studied owing to their many distinctive characteristics and applications such as catalysts in the fuel cell technology [14], gas sensor [15], catalytic wet oxidation [16][17], oxygen storage and release [18], wastewater treatment [19] or photo-catalytic oxidation of water [20].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it is reported that nanosized ceria show pH dependent oxidase activity, which can quickly oxidize a series of organic substrates [36,37]. The results provide new insights into the applications of ceria nanomaterials in medical diagnosis and biosensing.…”
Section: Introductionmentioning
confidence: 94%